MOF-derived intelligent arenobufagin nanocomposites with glucose metabolism inhibition for enhanced bioenergetic therapy and integrated photothermal-chemodynamic-chemotherapy - Lihua Chen; Jiaying Yang; Lingyu Jia; Xiaolu Wei; Huijun Wang; Zhuo Liu; Shan Jiang; Pengyue Li; Yanyan Zhou; Hongjie Wang; Nan Si; Baolin Bian; et al. (Journal of Nanobiotechnology)
Abstract Bioenergetic therapy based on tumor glucose metabolism is emerging as a promising therapeutic modality. To overcome the poor bioavailability and toxicity of arenobufagin (ArBu), a MOF-derived intelligent nanosystem, ZIAMH, was designed to facilitate energy deprivation by simultaneous interventions of glycolysis, OXPHOS and TCA cycle. Herein, zeolitic imidazolate framework-8 was loaded with ArBu and indocyanine green, encapsulated within metal–phenolic networks for chemodynamic therapy and hyaluronic acid modification for tumor targeting. ZIAMH nanoparticles can release ArBu in the tumor microenvironment for chemtherapy, and ICG enables photothermal therapy under near-infrared laser irradiation. In vitro and in vivo mechanism studies revealed that the ZIAMH nanoplatform downregulated glucose metabolism related genes, resulting in the reduction of energy substances and metabolites in tumors. Additionally, it significantly promoted cell apoptosis by upregulating pro-apoptotic proteins such as Bax, Bax/Bcl-2, cytochrome C. Animal studies have shown that the tumor inhibition efficiency of ZIAMH nanomedicines was three fold higher than that of free drugs. Therefore, this study provides a new strategy for glucose metabolism-mediated bioenergetic therapy and PTT/CDT/CT combined therapy for tumors. Graphical Abstract